2019
DOI: 10.1016/j.redox.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of microbial induced redox-dependent intestinal signaling

Abstract: Intestinal homeostasis is regulated in-part by reactive oxygen species (ROS) that are generated in the colonic mucosa following contact with certain lactobacilli. Mechanistically, ROS can modulate protein function through the oxidation of cysteine residues within proteins. Recent advances in cysteine labeling by the Isotope Coded Affinity Tags (ICATs) technique has facilitated the identification of cysteine thiol modifications in response to stimuli. Here, we used ICATs to map the redox protein network oxidize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…We previously reported that lactobacilli with gut epithelium induce ROS generation, with downstream influences on cell proliferation by mechanisms that require their mucus binding properties (Ardita et al, 2014). Indeed, epithelial ROS that is generated in response to bacteria functions in a signaling role, by which ROS-sensitive cellular enzymes could be influenced by bacterial-induced changes in redox status (Matthews et al, 2018). This hypothesis is supported by reports that reversible oxidative inactivation of a wide range of regulatory enzymes is a recognized mechanism of signal transduction (Ray et al, 2012).…”
Section: Plantarum Upregulates Upd2 Expression and Jak/stat Signalmentioning
confidence: 99%
“…We previously reported that lactobacilli with gut epithelium induce ROS generation, with downstream influences on cell proliferation by mechanisms that require their mucus binding properties (Ardita et al, 2014). Indeed, epithelial ROS that is generated in response to bacteria functions in a signaling role, by which ROS-sensitive cellular enzymes could be influenced by bacterial-induced changes in redox status (Matthews et al, 2018). This hypothesis is supported by reports that reversible oxidative inactivation of a wide range of regulatory enzymes is a recognized mechanism of signal transduction (Ray et al, 2012).…”
Section: Plantarum Upregulates Upd2 Expression and Jak/stat Signalmentioning
confidence: 99%
“…Therefore, increased intake and decreased efflux of cholesterol from macrophages have been identified as a key contributor to macrophage dysfunction, which is associated with the development of AS [ 5 , 6 ]. However, cholesterol metabolism homeostasis in macrophages under hyperlipidemia stress conditions has not been well studied [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biotin-iodoacetamide (BIAM) pull-down assay was performed, as described previously, 27 without modification. Briefly, epithelial cell monolayers were lysed, the insoluble material was removed by centrifugation, and the lysates were adjusted to 25 mmol/L (biotinylated iodoacetamide) BIAM and incubated on ice in the dark for 45 minutes.…”
Section: Biam Pull-down Assaymentioning
confidence: 99%
“…The Cleavable ICAT Reagent for Protein Labeling (stock keeping unit number 4339036) was obtained from SCIEX (Framingham, MA). Isotope-coded affinity tag (ICAT) and tandem mass spectrometry analysis was performed essentially, as previously described, 27 with minor modification. Briefly, trichloroacetic acid precipitated proteins from cell lysates were incubated with a heavy ICAT reagent to label reduced cysteines, followed by a second trichloroacetic acid precipitation, disulfide reduction with tris(2-carboxyethyl) phosphine (TCEP), and then labeling of newly reduced cysteines with a light ICAT reagent.…”
Section: Isotope-coded Affinity Tagsmentioning
confidence: 99%
See 1 more Smart Citation